2023
DOI: 10.3390/su152316471
|View full text |Cite
|
Sign up to set email alerts
|

Navigating Uncharted Waters: Exploring Leaders’ Challenges in the Era of COVID-19 and the Rise of Telework

Ingi Runar Edvardsson,
Johanna Gardarsdottir

Abstract: This paper presents a systematic literature review of the challenges faced by managers during COVID-19, with a focus on teleworking. The study consists of an analysis of 53 articles published in the period 2020–2023 in journals indexed in the Elsevier’s Scopus and Clarivate Analytics’ Web of Science databases. The inclusion criteria were: (1) peer-reviewed articles; (2) empirical articles; (3) written in English. Five themes were identified: Leadership Styles, Organizational Support and Communication, Telework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…It was also established that remote work can improve output capacity with appropriate hardware, training, and management, as well as the level of sustainable development by reducing commuting to work and providing for dignified work involving more independence and flexibility [40]. The studies of working at home adapted the operationalisation of Lefebvre's triad model in order to depict the workstations spatially (physical space, cyberspace, social space) for purposes of the analysis of securing developmental continuity in scope of the home office system, in particular ensuring continuity of education through home-office system [41].…”
Section: Home Officementioning
confidence: 99%
“…It was also established that remote work can improve output capacity with appropriate hardware, training, and management, as well as the level of sustainable development by reducing commuting to work and providing for dignified work involving more independence and flexibility [40]. The studies of working at home adapted the operationalisation of Lefebvre's triad model in order to depict the workstations spatially (physical space, cyberspace, social space) for purposes of the analysis of securing developmental continuity in scope of the home office system, in particular ensuring continuity of education through home-office system [41].…”
Section: Home Officementioning
confidence: 99%
“…From the familiar sphere perspective, although remote work can be considered a practice aimed at balancing the worklife relationship, teleworkers may easily feel that work intertwines with their family dynamics and vice versa, hindering balance in the aforementioned relationship [68][69][70]. Indeed, a study carried out by Edvardsson and Gardarsdottir [71] demonstrated that leaders' attitudes towards telework, along with other factors such as adequate equipment and training, were significant determinants of positive outcomes regarding the telework experience during the COVID-19 pandemic. On the other hand, due to the insecurity, stress, and general concern provoked by the pandemic, even those who worked on-site were likely to experience the erosion of work-family boundaries.…”
Section: Perceived Supervisory Family Support and Work Engagementmentioning
confidence: 99%